Hubungan Ketepatan Waktu Penyajian Dan Rasa Makanan Dengan Sisa Makanan Biasa Kelas Ii Dan Iii Di Rsud Raa Soewondo Pati - Umiyati, Yulis sri, Endang Nur Widyaningsih, S.ST.,M.Si,Med (2016)
Too many food waste causes problems of "Hospital Malnutrition" The high amount of food waste are caused by many factors, which is internal, external and others. Many food waste could cause patients lose nutrients. In RSUD RAA Soewondo Pati in 2013, the average amount of food waste is 27,1% and in 2014 is 31,56%. The purpose of this research is to know the correlation between time efficiency of serving and taste to food waste of second and third class patient in RSUD RAA Soewondo Pati. The design of this research is using cross-sectional approach. The subject of this research is the patients in general surgical room of RSUD RAA Soewondo Pati. The measured indicator in this research is time efficiency of the three meal time (morning, afternoon, evening), the food waste in each meal time, and patient's respond to meal's taste, and it's all documented in questionnaire. Those data is analized with Rank Spearman correlation and Pearson Product Moment. The time efficiency of distribution of breakfast, lunch and dinner are respectively 82,9%, 92,7%, and 95,1%. The result about meal's tastiness is that 67,5% patients respond that the meal taste good. The average waste of staple food (rice) is 63,4%, meat-based side dish is 63,4%, plant-based side dish is 78%, vegetable is 75,6%. The result of Rank Spearman correlation shows that the ρ value of time efficiency to food waste is ρ=0,377. The Pearson Product Moment result of ρ value of food's taste with food waste is ρ=0,298. There is no correlation between time efficiency of food serving ti food waste of second and third class patient in RSUD RAA Soewondo Pati.